Portrait of Elaine Steinbeck sitting next to a bronze bust of John Steinbeck - Junichi Takahashi:::Photographer:::::::::::: (2023)
Elaine Steinbeck, in her apartment, sits next to personal photographs and a bust of John Steinbeck. Photograph was taken for a Japanese magazine.